The sum of all values of x that satisfy
3 6 ( 5 x + 6 ) − 3 5 ( 6 x − 1 1 ) = 1 ,
can be expressed as n m , where m and n are coprime integers. Find m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can you explain the "after some bashing and substituting"? I get that
3 3 0 ( 5 x + 6 ) ( 6 x − 1 1 ) ( 3 6 ( 5 x + 6 ) + 3 5 ( 6 x − 1 1 ) ) = 3 0
but do not immediately see how you break it down into 2 equations.
Log in to reply
Sorry Sir, typo there! Fixed! Now it is fine!
Doesn't seem to be a question of level 5, don't you think?
Yes you are right ,the answer is n 2 .
Did same!!
Let's assume that 5 ( 6 x − 1 1 ) = n 3 … ( 1 ) For the given equation to be satisfied, the following must be true. 6 ( 5 x + 6 ) = ( n + 1 ) 3 … ( 2 ) Subtracting equation (1) from equation (2), 3 n 2 + 3 n + 1 = 3 6 + 5 5 ⟹ n 2 + n − 3 0 = 0 Hence we get:- n = 5 , n = − 6 From equation (1)
When n = 5 , we get , x = 6 .
When n = − 6 , we get, x = − 6 2 5 − 5 6 . Hence the sum of values of x is 3 0 1 9
EASIER. if x+y+z=0
then
x^3+y^3+z^3=3xyz
let Q be
A-B=1 (because i dont wanna type cube roots)
A-B-1=0
hence
A^3+(-B)^3+(-1)^3 = 3AB(-1)
this immediately removes the cube roots from A and B and give
6(5x+6)-5(6x-11)-1 = 3( (6(5x+6)5(6x-11) )^(1/3))
LHS is constant.
cube both sides and simplify and u get quadratic eqn.,Sum of roots is -b/a which
gives 19/30 hence
m+n=49
The best method ! Great
l e t a = 6 ( 5 x + 6 ) ∴ 5 ( 6 x − 1 1 ) = a − 9 1 S o w e h a v e 3 a − 3 a − 9 1 = 1 ⟹ 3 a − 1 = 3 a − 9 1 T a k i n g c u b e s a n d s i m p l y f i n g : − 3 a 3 2 + 3 a 3 1 + 9 0 = 0 Factoring this quadratic in a 3 1 w e g e t a 3 1 = 6 a n d − 5 ∴ 3 0 x + 3 6 = a = 2 1 6 a n d − 1 2 5 . S o m = 3 0 1 8 0 , n = 3 0 − 1 6 1 . n m = 3 0 1 8 0 + 3 0 − 1 6 1 = 3 0 1 9 m + n = 4 9
Write a = 3 6 ( 5 x + 6 ) and b = 3 5 ( 6 x − 1 1 ) . Then, note that a − b − 1 = 0 , a 3 − 6 ( 5 x + 6 ) = 0 , and b 3 − 5 ( 6 x − 1 1 ) = 0 . Then, re-write the left-hand sides of each of these three equations as l 1 , l 2 , and l 3 . Note that ( a 2 + a b + b 2 + a + 2 b + 1 ) l 1 − l 2 + l 3 = − 3 b 2 − 3 b + 9 0 = 0 , or ( b + 6 ) ( b − 5 ) = 0 . Then, we know that 5 ( 6 x − 1 1 ) = 1 2 5 or 5 ( 6 x − 1 1 ) = − 2 1 6 . Solving gives us x = 6 or x = − 3 0 1 6 1 , which have a sum of 3 0 1 9 .
Problem Loading...
Note Loading...
Set Loading...
I think you should add that "The answer is n 2 " again.
Cubing the equation,
6 ( 5 x + 6 ) − 5 ( 6 x − 1 1 ) − 3 3 3 0 ( 5 x + 6 ) ( 6 x − 1 1 ) ( 3 6 ( 5 x + 6 ) − 3 5 ( 6 x − 1 1 ) ) = 1
After some bashing and substituting 3 6 ( 5 x + 6 ) + 3 5 ( 6 x − 1 1 ) = 1 ,
9 0 = 3 3 3 0 ( 5 x + 6 ) ( 6 x − 1 1 )
3 0 = 3 3 0 ( 5 x + 6 ) ( 6 x − 1 1 )
Again cubing and a little bashing,
3 0 x 2 − 1 9 x − 9 6 6 = 0
Using Vieta,
Sum = 3 0 1 9
Hence, the answer is 4 9